2019
DOI: 10.1038/s41598-019-55196-6
|View full text |Cite
|
Sign up to set email alerts
|

One-year mortality after hip fracture surgery and prognostic factors: a prospective cohort study

Abstract: Older adult patients with hip fractures are 3–4 times more likely to die within one-year after surgery than general population. The study aimed to identify independent predictive factors associated with one-year mortality after hip fracture surgery. A prospective prognostic cohort study was performed. All patients aged ≥65 years, consecutively admitted in three Italian hospitals with a diagnosis of fragility hip fracture were included. Patients with periprosthetic or pathological fractures were excluded. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
68
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 33 publications
10
68
0
6
Order By: Relevance
“…In this meta-analysis, there was no significant difference in mortality within 1 year and within 2 years between the internal fixation group and the hemiarthroplasty group. Morri 24 points out that the main causes of death within 1 year of hip fracture were older age, more comorbidities, and physical weakness. The degree of hip function recovery affects patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, there was no significant difference in mortality within 1 year and within 2 years between the internal fixation group and the hemiarthroplasty group. Morri 24 points out that the main causes of death within 1 year of hip fracture were older age, more comorbidities, and physical weakness. The degree of hip function recovery affects patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…These studies followed apparently healthy individuals without cancer at baseline [ 10 , 29 , 30 ]; thus, whether dietary acid load is associated with total and cancer-specific mortality among cancer survivors cannot be concluded from these studies. Dietary acid load has been shown to increase the risk of hypertension, diabetes, chronic kidney diseases, and hip fractures in cohort studies [ 31 , 32 , 33 , 34 , 35 ]; all of these are risk factors for total mortality [ 36 , 37 , 38 ]. Furthermore, animal studies have shown that metabolic acidosis can lead to increased cancer development and metastasis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Частота переломів даної локалізації прогресивно збільшується з віком, переважає в жінок і пов'язана з прогресуючою втратою міцності кісткової тканини й розвитком системного остеопорозу. Проведені останніми роками дослідження продемонстрували, що показники летальності у хворих з переломами ПВСК найбільші протягом першого року після перелому [5,6,8].…”
Section: -міс виживаністьunclassified
“…Поворознюка [5] та R. Civinini [9], 22 % у дослідженні M. Gurger [10], 27 % у дослідженні I.S. Cenzer [11] та 33 % у дослідженні O. Guzon-Illescas [8].…”
Section: -міс виживаністьunclassified